EFEKTIVITAS METODE MEMBACA BUKU CERITA DALAM MENINGKATAN KEPEKAAN SOSIAL ANAK USIA DINI - Fuadah, Anisatul; Diana, Raden Rachmy (Raudhah - Proud To Be Professional, 2025)
This study explores the effectiveness of storybook reading in enhancing social awareness among early childhood learners. In the digital era, children’s direct social interactions are declining due to excessive use of gadgets, leading to decreased empathy and social awareness. This study used a quasi-experimental design with pre-test and post-test control groups. The experimental group was exposed to a structured storybook reading session, while the control group followed the conventional learning method. Data collection included observation, and Social Skills Rating System (SSRS) assessment, which were analyzed using statistical tests such as N-Gain and independent t-test, etc. The findings revealed a significant difference between the experimental and control groups, with the experimental group showing a higher mean increase in social awareness (N-Gain = 0.5903) compared to the control group (N-Gain = 0.1117). The independent t-test also confirmed a statistically significant difference (p < 0.05) in the increase in social awareness. These results suggest that storybook reading is an effective method to foster children’s social awareness. This study contributes to the development of early childhood education methodology by emphasizing the role of stories in shaping children's social-emotional skills.